Physical and chemical properties of soils collected from surrounding areas of Payra thermal power plant: Physical and chemical properties of coastal soils (Journal of Bangladesh Academy of Sciences, 2024)
The study was conducted to observe the physical and chemical properties of the soils of the Payra thermal power plant's surrounding areas. The textural class of 55 collected soil samples was mostly Silt loam, with few Silty clay loam soils. Soil pH ranges from 3.72 to 7.82, with more than 80 % being acidic and only 4% slightly alkaline. The 23 % of samples were highly acidic (pH